"They make a difference": a qualitative study of providers' experiences of peer support in outpatient clinics for people living with HIV - Anita Øgård-Repål; Rigmor C. Berg; Vegard Skogen; Mariann Fossum (BMC, 2022)
Abstract Background Although the life expectancy of people living with HIV has increased, they are still often disconnected from society through stigma and discrimination. Peer support has been found to increase social support. Given the limited research on peer support from the providers' perspective, this study explored how peer supporters experience their roles and contributions in outpatient clinics (OPCs). Additionally, healthcare professionals' perceptions of working with peer supporters in OPCs were examined.  Methods This qualitative study included purposively selected peer supporters (n = 10) and healthcare professionals (n = 5) from five OPCs in Norway in 2020. In-depth interviews and focus group discussions were conducted in Norwegian or English, using interview guides. Interview transcripts were analysed in NVivo 12 using reflexive and collaborative thematic analysis. Results The results show that peer supporters experience mutual support through emotional and honest interactions. Further, the peer supporters found it essential to negotiate with the service users about their preconception of HIV, confront their views through dialogue, and replicate positive experiences by being credible role models. The participants expressed that integrating peer support in the OPCs' usual care processes increased the prospect of equitable services. Quality of peer support and role clarity were identified as critical components. The results demonstrate that emotional and honest conversations promote support between peers and that peer supporters identify a need for a reframed understanding of HIV by modelling plausible alternative interpretations and coping experiences. Conclusions This study contributes to knowledge on how peer support can meet the needs of people living with HIV. Incorporating people living with HIV in the co-production and distribution of healthcare services may improve the knowledge and perspectives in healthcare services. However, the skill standards of peer supporters should be addressed when implementing peer support in usual care.